2017
DOI: 10.7860/jcdr/2017/25859.10424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ondansetron on Prevention of Ventilator Associated Pneumonia in Intensive Care Unit Patients in Kashani Hospital in 2013

Abstract: Introduction: Ventilator Associated Pneumonia (VAP) is the second most common infection with high mortality (24-50%). Ondansetron is a reliable and safe drug and it is currently used in the prevention of nausea and vomiting and has no side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Furthermore, although no statistical difference was observed in the two groups after PSM in this study, the VAP incidence tended to decrease in the ondansetron group before and after PSM. Madineh et al ’s ( 32 ) study also showed that VAP in the ondansetron group was less prevalent than in the non-ondansetron group (12.5% vs. 15%). However, the sample size of 40 participants in their study was relatively small.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, although no statistical difference was observed in the two groups after PSM in this study, the VAP incidence tended to decrease in the ondansetron group before and after PSM. Madineh et al ’s ( 32 ) study also showed that VAP in the ondansetron group was less prevalent than in the non-ondansetron group (12.5% vs. 15%). However, the sample size of 40 participants in their study was relatively small.…”
Section: Discussionmentioning
confidence: 89%
“…Çalışma sonucunda nebülize kolistinin VİP insidansında anlamlı bir etkisinin olmadığını saptanmıştır (64). Madineh ve arkadaşlarının (2017) çalışma sonucu 4mg ondansetron uygulanan deney grubunda VİP insidansının kontrol grubundan daha düşük olduğunu, ancak bu farkın anlamlı olmadığını göstermiştir ve ayrıca çalışma sonucunda Ondansetron'un VİP önleme üzerinde etkisinin olmadığı tespit edilmiştir (76). van Delden ve arkadaşları (2012) tarafından yürütülen çalışmada 300 mg/ gün azitromisin verilen hastalarda VİP insidansında azalma eğiliminin olduğunu ve buna ek olarak azitromisinin, VİP riski yüksek olan hastalarda VİP'i önemli ölçüde önlediği sonuna varılmıştır (46).…”
Section: çAlışmalardan Elde Edilen Bulgularunclassified